Examination of In-Service Trainings in Terms of Functionality and Meeting the Needs and Expectations of Physical Education Teachers - Mehmet Asma; Diyar Kaya Saylam; Deniz Şenavcı; Hüseyin Çamliyer; Hatice Çamliyer (Journal of Educational Issues, 2024)
Teacher’s in-service training is considered a lifelong learning activity to gain the knowledge, skills, and competencies they will need throughout their careers and to enable them to perform their profession more effectively. The surveys reveal the existence of various problems in these in-service training activities. This study aims to examine the problems encountered in the in-service training conducted for physical education (PE) teachers and the level of meeting their needs and expectations. The research was carried out under a mixed method. 302 teachers (private n = 131; public n = 171) who work in Manisa and Izmir provinces constitute the sample group of the research. Quantitative data were obtained by using the “In-Service Training Evaluation Scale” developed by Uçar (2005). Qualitative interview forms developed by the researchers were used to obtain qualitative data. Data obtained from interviews with five private and five public school PE teachers were recorded and analyzed by the descriptive analysis method. While there was a significant difference in favor of male teachers in the “necessity of training” sub-dimension, no difference was found between the average scores obtained from the teachers according to the gender variable. According to the data obtained from the qualitative interviews, the public school teachers interviewed agree on the inadequacy of the training. Based on the data obtained, it is possible to say that in-service training activities offered to private school teachers are carried out more effectively. When the results obtained from quantitative and qualitative data are compared, it is understood that the training in public schools is far from meeting teacher needs and expectations. The ineffectiveness of training and the inadequacy of educators are among the main problems that arise in terms of public schools.